2012
DOI: 10.1016/j.jnutbio.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish (Danio rerio) fed vitamin E-deficient diets produce embryos with increased morphologic abnormalities and mortality

Abstract: Vitamin E (α-tocopherol) is required to prevent fetal resorption in rodents. To study α–tocopherol’s role in fetal development, a non-placental model is required. Therefore, the zebrafish, an established developmental model organism, was studied by feeding the fish a defined diet with or without added α–tocopherol. Zebrafish (age: 4–6 w) were fed the deficient (E-), sufficient (E+), or lab diet up to 1 y. All groups showed similar growth rates. The exponential rate of α–tocopherol depletion up to ~80 day in E-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 40 publications
4
74
0
Order By: Relevance
“…Adult zebrafi sh were kept under standard laboratory conditions at 28.5°C with a 14 h light/10 h dark cycle. For 9 months, beginning at 50 days postfertilization, zebrafi sh were fed defi ned diets, which contained only fatty acids shorter than 18 carbons with two or three double bonds ( 2,5,9 ), were prepared in 300 g batches with the vitamin C source as StayC (500 mg/kg; Argent Chemical Laboratories Inc.) without (E Ϫ ) or with (E+) added vitamin E (500 mg RRR -␣ -tocopheryl acetate/kg diet; ADM, Decatur, IL), as described previously ( 5 ). Diets were stored at Ϫ 20°C until fed to the zebrafi sh.…”
Section: Zebrafi Sh Housing and Feedingmentioning
confidence: 99%
“…Adult zebrafi sh were kept under standard laboratory conditions at 28.5°C with a 14 h light/10 h dark cycle. For 9 months, beginning at 50 days postfertilization, zebrafi sh were fed defi ned diets, which contained only fatty acids shorter than 18 carbons with two or three double bonds ( 2,5,9 ), were prepared in 300 g batches with the vitamin C source as StayC (500 mg/kg; Argent Chemical Laboratories Inc.) without (E Ϫ ) or with (E+) added vitamin E (500 mg RRR -␣ -tocopheryl acetate/kg diet; ADM, Decatur, IL), as described previously ( 5 ). Diets were stored at Ϫ 20°C until fed to the zebrafi sh.…”
Section: Zebrafi Sh Housing and Feedingmentioning
confidence: 99%
“…A total of 10 μL reaction system was prepared for real-time quantitative polymerase chain reaction (RT-qPCR) using SYBR Green Master Mix (TaKaRa). The sequences of used primers were flk1 forward 5′-GAGAACGGAACCAACAAGATCCAC GAG-3′ reverse 5′-CCCTCCAGCAGAACTGACTCCTTAC-3′ p53 forward 5′-ACCACTGGGACCAAACGTAG-3′ reverse 5′-CAGAGTCGCTTCTTCCTTCG-3′, 32 AIF forward 5′-AAAGTCCGGAAAGAGGGTGT-3′ reverse 5′-GCCTGGAGCTCAGCATTAAC-3′, 33 β -actin forward 5′ -CTGTCTTCCCATCCATCG TGGGTC-3′ reverse 5′-CTCCATATCATCCCAGTTGGTGACA-3′.…”
Section: Rna Isolation and Quantitative Rt-pcrmentioning
confidence: 99%
“…Comments received: 6. It was suggested that epidemiological studies may provide a better representation of the general population than randomised controlled trials (RCTs).…”
Section: Criteria On Which To Base Drvsmentioning
confidence: 99%
“…The importance of vitamin E in protecting polyunsaturated fatty acids (PUFAs) against oxidation in humans was emphasised. Research on the effects of vitamin E deficiency in mice (Tanito et al, 2007) and zebrafish (Danio reio) (Miller et al, 2012; Lebold et al, 2013) was referred to in order to support the importance of vitamin E in cellular membranes high in docosahexaenoic acid (DHA) and arachidonic acid (AA) in the brain, nervous system, retina, and reproductive system, and therefore development in early life.2. It was added that the vitamin E presence in cell membranes (preferentially in non-raft domains) is well documented .…”
mentioning
confidence: 99%
See 1 more Smart Citation